The use of analytical techniques for qualitative differentiation of lipids extracted from cheese samples and lard - Alkhalf, Maha; Mirghani, Mohamed Elwathig Saeed; Marikkar, Mohammed Nazrim; Kabbashi, Nassereldeen Ahmed; Hammed, Ademola Monsur; Kabbashi, N.A (WFL Publisher Ltd., 2017)
A study was carried out to differentiate three different types of cheese lipids from lard using GC-MS, Fourier transform infrared (FTIR) spectrometry and Differential Scanning Calorimetry (DSC). Sample of the cheese lipids and lard were extracted and analyzed using these three instruments. Results showed that all three cheese types were found to possess short chain fatty acids (C4 to C12) while these were totally absent in lard. FTIR spectroscopy corresponds to the wavenumbers at 3007, 1140 –1070, 756 and 720 cm–1 in the spectrum were useful to differentiate between these cheese lipid types and lard. DSC cooling and heating curves displayed considerable differences in their profiles that can be helpful to distinguish the three cheese lipid types from lard. It could be concluded that GC-MS, FTIR spectroscopy and DSC are rapid and steadfast techniques for the detection of non-halal and/or non-kosher lipids in the cheese.